2012
DOI: 10.1002/jbmr.1701
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C–delta deficiency perturbs bone homeostasis by selective uncoupling of cathepsin K secretion and ruffled border formation in osteoclasts

Abstract: Bone homeostasis requires stringent regulation of osteoclasts, which secrete proteolytic enzymes to degrade the bone matrix. Despite recent progress in understanding how bone resorption occurs, the mechanisms regulating osteoclast secretion, and in particular the trafficking route of cathepsin K vesicles, remain elusive. Using a genetic approach, we describe the requirement for PKCδ in regulating bone resorption by affecting cathepsin K exocytosis. Importantly, PKCδ deficiency does not perturb formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 43 publications
9
42
0
Order By: Relevance
“…8F) are also consistent with the fact that treatment of mice with enzastaurin, a PKCb inhibitor, can reduce osteoclastic bone destruction caused by metastatic breast cancer cells (Dudek et al 2008). Interestingly, Cremasco et al (2012) have shown that another PKC, PKCd, was also required for osteoclast function in vivo because it promotes cathepsin K exocytosis. Together, these and our findings suggest that multiple members of the PKC family might contribute nonredundantly to the resorptive function of osteoclasts.…”
Section: Lysosomal Biogenesis In Osteoclasts Genes and Development 965supporting
confidence: 76%
“…8F) are also consistent with the fact that treatment of mice with enzastaurin, a PKCb inhibitor, can reduce osteoclastic bone destruction caused by metastatic breast cancer cells (Dudek et al 2008). Interestingly, Cremasco et al (2012) have shown that another PKC, PKCd, was also required for osteoclast function in vivo because it promotes cathepsin K exocytosis. Together, these and our findings suggest that multiple members of the PKC family might contribute nonredundantly to the resorptive function of osteoclasts.…”
Section: Lysosomal Biogenesis In Osteoclasts Genes and Development 965supporting
confidence: 76%
“…In vitro experiments were repeated with bone marrow from both mice of C57BL/6-129 and C57BL/6 background. Analysis of bone phenotype by microCT and histology was performed as described (37). All experiments were approved by the Washington University School of Medicine animal care and use committee.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether ActA treatment decreased mature OCLmediated bone resorption, functional measurements of OCL activity were employed (Cremasco et al, 2012). First, mature OCLs were treated with combinations of RANKL and ActA in the presence of bovine bone powder.…”
Section: Activin a Suppresses Mature Osteoclastsmentioning
confidence: 99%